Answer:
Value of 43 – 10 ÷ 2 + [(7 + 3) • 3] is 68 .
Explanation:
As the expression given in the question be as follow .
= 43 – 10 ÷ 2 + [(7 + 3) • 3]
It also written as
![= 43 - (10)/(2)+ [(7+3)* 3]](https://img.qammunity.org/2018/formulas/mathematics/middle-school/8zhdervp3qm35pj53wfurmedcj2z49efc2.png)
![= 43 - 5+ [7* 3+3* 3]](https://img.qammunity.org/2018/formulas/mathematics/middle-school/fcnhsm465363vf4mf1taj4mse4t0v4xs7b.png)
![= 43 - 5+ [21+9]](https://img.qammunity.org/2018/formulas/mathematics/middle-school/peteey1r684i2fsaeftds94yyel23o2liv.png)
![= 43 - 5+ [30]](https://img.qammunity.org/2018/formulas/mathematics/middle-school/887uasi12i2qyx9smorf2xloahdl6y8lyd.png)
= 43 -5 +30
= 73 -5
= 68
Therefore the value of 43 – 10 ÷ 2 + [(7 + 3) • 3] is 68 .